On the Philosophical Determination of Literature - Jason Kemp Winfree (Humanities, 2018)
This paper traces the influence of German Idealism on the conceptions of literature proffered by Bataille and Blanchot, and it aims to show how that influence registers as a proto-ethics. In the demand that freedom be actualized in the world, German Idealism frames the determination of literature as one-sided, subjective, and abstract. Literary expression is never adequate to what it represents. Precisely because it has no direct bearing on the world of action, however, literature is free to pursue that which the world of action excludes: the density and obscurity of existence itself. In this pursuit, literature recasts the philosophical aspiration of self-knowledge in terms of a fidelity to existence and life in excess of individuality.